2022
DOI: 10.18388/abp.2020_5624
|View full text |Cite
|
Sign up to set email alerts
|

The role of GRP78 in oxidative stress induced by tunicamycin in trabecular meshwork cells

Abstract: Objective: To clarify the regulatory effect of GRP-78 induced by tunicamycin on endoplasmic reticulum (ER) stress. Methods: Tunicamycin was used to induce ER stress in trabecular meshwork cells (HTMC and GTM3). Cell apoptosis and ROS content were detected by flow cytometry to reveal the effect of tunicamycin on trabecular meshwork cells. Results: Tunicamycin could significantly increase the ROS content and the apoptosis rate in HTMC and GTM3 (p<0.01). The results showed that tunicamycin could increase the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In human glaucom TMCs, resveratrol has been reported to reduce the expression of proinflamm ER-related oxidative stress has been reported in both TMCs and RGCs in the context of glaucomatous optic neuropathy. Studies on TMCs have demonstrated the involvement of the PERK-eIF2α-ATF4-CHOP cascade in glaucomatous TM, both in human and murine cells, highlighting the activation of this pathway in glaucoma [245][246][247][248]. Similarly, various studies have described the implication of the PERK-eIF2α-ATF4-CHOP pathway in RGC loss [249][250][251][252].…”
Section: Therapeutic Potential Of Natural Compounds In Glaucomamentioning
confidence: 98%
“…In human glaucom TMCs, resveratrol has been reported to reduce the expression of proinflamm ER-related oxidative stress has been reported in both TMCs and RGCs in the context of glaucomatous optic neuropathy. Studies on TMCs have demonstrated the involvement of the PERK-eIF2α-ATF4-CHOP cascade in glaucomatous TM, both in human and murine cells, highlighting the activation of this pathway in glaucoma [245][246][247][248]. Similarly, various studies have described the implication of the PERK-eIF2α-ATF4-CHOP pathway in RGC loss [249][250][251][252].…”
Section: Therapeutic Potential Of Natural Compounds In Glaucomamentioning
confidence: 98%
“…ER-related oxidative stress has been reported in both TMCs and RGCs in the context of glaucomatous optic neuropathy. Studies on TMCs have demonstrated the involvement of the PERK-eIF2α-ATF4-CHOP cascade in glaucomatous TM, both in human and murine cells, highlighting the activation of this pathway in glaucoma [252][253][254][255]. Similarly, various studies have described the implication of the PERK-eIF2α-ATF4-CHOP pathway in RGC loss [256][257][258][259].…”
Section: Interplay Between Mitochondrial and Er Stress In Tmcs And Rgcsmentioning
confidence: 98%